Female hyperandrogenism in elite sports and the athletic triad - Hirschberg, A. L. (Seminars in Reproductive Medicine, 2022)
Essential hyperandrogenism seems to be overrepresented in female elite athletes. This applies to mild forms such as polycystic ovary syndrome, as well as rare differences/disorders of sex development (DSD). The reason is likely a selection bias since there is increasing evidence that androgens are beneficial for athletic performance by potent anabolic effects on muscle mass and bone mass, and stimulation of erythropoiesis. XY DSD may cause a greatly increased production of testosterone in the male range, that is, 10 to 20 times higher than the normal female range. The established regulations concerning the eligibility of female athletes with severe hyperandrogenism to compete in the female classification remain controversial. The most common cause of menstrual disorders in female athletes, however, is probably an acquired functional hypothalamic disturbance due to energy deficiency in relation to energy expenditure, which could lead to low bone mineral density and increased risk of injury. This condition is particularly common in endurance and esthetic sports, where a lean body composition is considered an advantage for physical performance. It is important to carefully evaluate endocrine disturbances and menstrual disorders in athletes since the management should be specific according to the underlying cause.